2014
DOI: 10.1111/lam.12328
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Salmonella spp. by a loop-mediated isothermal amplification (LAMP) method targeting bcfD gene

Abstract: A loop-mediated isothermal amplification (LAMP) assay was established to detect Salmonella targeting bcfD gene, a conserved fimbrial operon gene. The detection limit was 5 CFU of Salmonella pure culture or 200 CFU of artificially spiked faeces per reaction system (equivalent to 5000 CFU g(-1) of faeces), and this method could directly detect Salmonella in chicken faeces free of pre-enrichment in a reaction time of 25 min. The Salmonella LAMP assay is a rapid, sensitive, specific and practical method for Salmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 23 publications
3
31
1
Order By: Relevance
“…100%. The specificity results (100%) observed in present study are also in accordance with Zhuang et al, (2014) who reported that LAMP technique could amplify all the 44 Salmonella strains successfully, but none of 9 non-Salmonella standard strains used under study.…”
Section: Analysis Of Field Samplessupporting
confidence: 80%
See 2 more Smart Citations
“…100%. The specificity results (100%) observed in present study are also in accordance with Zhuang et al, (2014) who reported that LAMP technique could amplify all the 44 Salmonella strains successfully, but none of 9 non-Salmonella standard strains used under study.…”
Section: Analysis Of Field Samplessupporting
confidence: 80%
“…This method relies on the auto-cycling strand displacement nature of Bst DNA polymerase with high strand displacement activity and a set of two specially designed inner and two outer primers. This novel method can amplify a few copies of DNA to 10 9 copies in less than an hour under isothermal conditions (60-65°C) (Zhuang et al, 2014). The expensive equipment like thermocycler is not necessary to give a high level of precision, equivalent or greater, when compared to PCR.…”
Section: Issn: 2319-7706 Volume 6 Number 4 (2017) Pp 2523-2532mentioning
confidence: 99%
See 1 more Smart Citation
“…Because Bst DNA polymerase works under isothermal conditions, special devices such as thermal cyclers are unnecessary. LAMP is widely used in medical, biological, and agricultural research (15,16). In the present study, we combined PCR and LAMP (PCR-LAMP) in an attempt to develop a highly sensitive method for identification of P. gingivalis in formalin-fixed paraffin embedded (FFPE) chronic apical periodontitis tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with PCR, nucleic acid hybridization including loop-mediated isothermal amplification is portable, rapid and easy to operate [10]. However, the dependence on a relatively high temperature (63°C) and DNA extraction step still limit the practical application of these methods [11,12]. Due to the specificity of the selected aptamer, aptamer-based sensors are mainly used for rapid detection of common serotypes such as S. typhimurium and S. enteritidis, rather than detection of the genus [5,13,14].…”
Section: Introductionmentioning
confidence: 99%